Thực trạng hoạt động giáo dục phòng ngừa tai nạn thương tích cho học sinh tại một số trường tiểu học huyện Hóc Môn, Thành phố Hồ Chí Minh - Đoàn, Thuỵ Liên Hương; Nguyễn, Thị Ngọc Bé (Tạp chí Giáo dục, 2024)
Injury prevention education for students, especially primary school students, is an important task of schools, families and educational forces. This article evaluates and analyzes the current status of accident injury prevention education for students in primary schools in Hoc Mon district, Ho Chi Minh City, based on the approach to the elements of the educational process (including goals, content, forms, methods of education and testing, and evaluation of student’s academic outcomes). The survey results indicate that most of the surveyed activities are carried out quite frequently, with fairly satisfactory outcomes. However, there are still some existing problems and shortcomings, specifically teachers’ skills in organizing educational activities are limited, the time allocated for educating accident and injury prevention skills is not much, and facilities and teaching equipment for accident and injury prevention education activities are still lacking. The evaluation of the results of injury prevention education for students has not been carried out systematically, and assessment tools are lacking. The research results will be an important practical basis for proposing measures to improve the effectiveness of accident injury prevention education for students in primary schools.